Types and Role of Pollinators in Pollination – A Comprehensive Review - D. Herin Sheeba Gracelin,; S. Suga,; M. Muthu Sheeba,; N. Sinthiya, (The Bioscan, 2025)
Pollination is a fundamental biological process essential for the reproduction of flowering plants and the production of fruits and seeds. Pollinators—ranging from insects and birds to mammals and wind—play a critical role in facilitating pollen transfer, ensuring genetic diversity, and sustaining ecosystems. This review provides a comprehensive overview of the various types of pollinators, including entomophilous (insect) pollinators such as bees, butterflies, moths, beetles, and flies; ornithophilous (bird) pollinators; chiropterophilous (bat) pollinators; and abiotic pollination mechanisms like wind and water. The ecological and economic significance of pollinators is discussed, emphasizing their contribution to agricultural productivity and biodiversity conservation. Recent studies highlight alarming declines in pollinator populations due to habitat loss, pesticide use, climate change, and diseases, posing serious threats to global food security. The review concludes with a call for integrated conservation strategies, habitat restoration, and sustainable agricultural practices to protect pollinators and maintain ecosystem services.